Attitude control of flexible space structures using extended state observer - Mahawan, Bagus; Luo, Zheng-Hua; Han, Jing-Qing (Computer Assisted Methods in Engineering and Science, 2001)
In this paper, we construct a nonlinear Extended State Observer (ESO) to estimate the dynamics of linear or nonlinear systems with parameter uncertainties and unknown external disturbances. We then apply ESO to the high-precision attitude control of a flexible satellite whose dynamics are unknown. Simulation results demonstrate the usefulness of the proposed control method.